Associations of plasma TMAO and its precursors with stroke risk in the general population: A nested case‐control study. (6th October 2022) - Liu, Dong; Gu, Shujun; Zhou, Zhengyuan; Ma, Ze; Zuo, Hui
Abstract: Background: Trimethylamine N‐oxide (TMAO) is a gut‐derived atherogenic metabolite. However, the role of TMAO and its precursors in the development of stroke remains unclear. We aimed to examine the associations between metabolites in TMAO biosynthesis and stroke risk. Methods: A nested case‐control study was performed in a community‐based cohort (2013–2018, n = 16, 113). We included 412 identified stroke cases and 412 controls matched by age and sex. Plasma carnitine, choline, betaine, trimethyl lysine (TML), and TMAO were measured by ultrahigh performance liquid chromatography–tandem mass spectrometry. Conditional logistic regression analyses were used to calculate odds ratios (ORs) and their 95% confidence intervals (CIs) between these biomarkers and stroke risk. Results: After adjustment for body mass index, smoking, hypertension, educational attainment, and estimated glomerular filtration rate, the corresponding OR for the highest versus lowest quartile was 1.74 (95% CI: 1.16–2.61, P trend = 0.006) for total stroke and 1.81 (95% CI: 1.14–2.86, P trend = 0.020) for ischemic stroke in an essentially linear dose–response fashion. A significant association between TMAO and nonischemic stroke was shown as a J‐shape with OR for the highest versus second quartile of 5.75 (95% CI: 1.73–19.1). No meaningful significant risk association was found among plasma carnitine, choline, betaine, and TML with stroke risk. Conclusions: Increased TMAO was associated with higher stroke risk in the community‐based population, whereas the TMAO precursors carnitine, choline, betaine, and TML were not associated. Further studies are warranted to confirm these findings and to further elucidate the role of TMAO in the development of stroke. Abstract :